Front and Back Movement Analysis of a Triangle-Structured Three-Wheeled Omnidirectional Mobile Robot by Varying the Angles between Two Selected Wheels - A. P. Mohanraj; A. Elango; Mutra Chanakya Reddy (The Scientific World Journal)
Omnidirectional robots can move in all directions without steering their wheels and it can rotate clockwise and counterclockwise with reference to their axis. In this paper, we focused only on front and back movement, to analyse the square- and triangle-structured omnidirectional robot movements. An omnidirectional mobile robot shows different performances with the different number of wheels and the omnidirectional mobile robot’s chassis design. Research is going on in this field to improve the accurate movement capability of omnidirectional mobile robots. This paper presents a design of a unique device of Angle Variable Chassis (AVC) for linear movement analysis of a three-wheeled omnidirectional mobile robot (TWOMR), at various angles (θ) between the wheels. Basic mobility algorithm is developed by varying the angles between the two selected omnidirectional wheels in TWOMR. The experiment is carried out by varying the angles (θ = 30°, 45°, 60°, 90°, and 120°) between the two selected omniwheels and analysing the movement of TWOMR in forward direction and reverse direction on a smooth cement surface. Respectively, it is compared to itself for various angles (θ), to get its advantages and weaknesses. The conclusion of the paper provides effective movement of TWOMR at a particular angle (θ) and also the application of TWOMR in different situations.